2018
DOI: 10.1136/practneurol-2018-001959
|View full text |Cite
|
Sign up to set email alerts
|

Long QT syndrome masquerading as epilepsy

Abstract: The diagnosis of epilepsy is incorrect in up to 20% of cases so should be revisited if attacks are not responding to treatment. We present a case of long QT syndrome that remained undiagnosed in the epilepsy clinic for 15 years until a near-fatal arrhythmia revealed the diagnosis and allowed effective treatment of her attacks. We hope this near miss raises awareness of long QT syndrome as a potentially fatal, rare but treatable condition that neurologists must consider in people with a label of refractory epil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…The relationship between epilepsy and LQTS is complicated. Seizures can lead to QT prolongation [11][12][13], while LQTS can induce epileptic seizures; the two diseases can even be present together [14,15]. Verrier et al even proposed the concept of "epileptic heart", suggesting that recurrent seizures could lead to repeated surges of plasma catecholamines and hypoxemia that lead to electrical and mechanical dysfunction of cardiac cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The relationship between epilepsy and LQTS is complicated. Seizures can lead to QT prolongation [11][12][13], while LQTS can induce epileptic seizures; the two diseases can even be present together [14,15]. Verrier et al even proposed the concept of "epileptic heart", suggesting that recurrent seizures could lead to repeated surges of plasma catecholamines and hypoxemia that lead to electrical and mechanical dysfunction of cardiac cells.…”
Section: Discussionmentioning
confidence: 99%
“…Among them, TdP and ventricular fibrillation are key pointers to immediate drug withdrawal, and they are also the main causes of death. diLQTS caused by ASMs should be alerted, and ASMs should be stopped immediately upon the co-occurrence of TdP and ventricular fibrillation [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22]. The risk of Tdp can be increased in the cases of prolonged QTc, t-U wave malformation and T wave electric alternation.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the pathogenicity data of the variants in the three genes were mostly related to arrhythmia, which indicated that little is known about the pathogenicity of these variants in epilepsy. On the other hand, there is also an unneglectable chance of LQTS being misdiagnosed as epilepsy because LQTS‐related symptoms can often be attributed to alternative diagnoses, most commonly seizure disorders, as shown in a systematic retrospective review of 31 LQTS patients (MacCormick et al., ) and some other case reports (Galtrey, Levee, Arevalo, & Wren, ; Gatto, Fernandez Pardal, Micheli, Gonzalez, & Daru, ; Gatto, Zurru, & Gonzalez, ; Goyal, Sethi, & Shah, ). This kind of misdiagnosis could also be one explanation for the relatively high proportion of variant‐positive patients in the studied epilepsy cohort.…”
Section: Discussionmentioning
confidence: 99%
“…This may also assist in the management of some cardiac arrhythmias that can mimic epilepsy, such as long QT syndrome. 13 In the absence of joint clinics, physicians need to communicate more closely about these patients.…”
Section: Management Challengesmentioning
confidence: 99%